2013
DOI: 10.4317/medoral.18693
|View full text |Cite
|
Sign up to set email alerts
|

All-trans retinoic acid restores gap junctional intercellular communication between oral cancer cells with upregulation of Cx32 and Cx43 expressions in vitro

Abstract: Objective: All-trans retinoic acid (ATRA) has been demonstrated to inhibit tumor growth by restoration of gap junctional intercellular communication (GJIC) via upregulation of connexin (Cx) expression in some solid tumors. However, the relationship between ATRA and GJIC remains unclear in oral squamous cell carcinoma (OSCC). The aim of this study was to investigate the effect of ATRA on the GJIC function of OSCC. Study design: We measured the effects of ATRA on the viability and cell cycle distribution of SCC9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…20 μL of MTT solution (Merck KGaA, Darmstadt, Germany) was added to each well and incubated for 4 hours at 37°C and then 150 μL of dimethylsulfoxide (DMSO; Merck, Darmstadt, Germany) was added. Absorbance was measured by automated microplate reader (Thermo Fisher Scientific, Waltham, MA, USA) at 490 nm …”
Section: Methodsmentioning
confidence: 99%
“…20 μL of MTT solution (Merck KGaA, Darmstadt, Germany) was added to each well and incubated for 4 hours at 37°C and then 150 μL of dimethylsulfoxide (DMSO; Merck, Darmstadt, Germany) was added. Absorbance was measured by automated microplate reader (Thermo Fisher Scientific, Waltham, MA, USA) at 490 nm …”
Section: Methodsmentioning
confidence: 99%
“…Previous research has shown that exposure to all‐trans retinoic acid (ATRA) results in the increased expression of CX43, and subsequent increased gap junctional intercellular communication (GJIC), in multiple cell types including human leukemic bone marrow stromal cells, human oral cancer cells, and canine primary lens epithelial cells (Liu et al, ; Long et al, ; Wang et al, ). CX43′s structure plays an important role in its regulation by the cell, with a long cytoplasmic C‐terminal tail that contains several phosphorylation sites (Solan & Lampe, ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that exposure to all-trans retinoic acid (ATRA) results in the increased expression of CX43, and subsequent increased gap junctional intercellular communication (GJIC), in multiple cell types including human leukemic bone marrow stromal cells, human oral cancer cells, and canine primary lens epithelial cells (Liu et al, 2015;Long et al, 2010;Wang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…RA activates or represses target genes through the activation of two members of the nuclear receptor super family, retinoic acid receptors and retinoid X receptors (RXRs), binding to the retinoic acid response element (RARE) in target genes (14)(15)(16). In some cancer studies (17)(18)(19), RA has been found to alter the phosphorylation status of the Cx43 protein. Only a few studies have demonstrated the regulation relationship between RA and Cx43 in heart development (20), and the phosphorylation status is not a main cause of heart defects (10).…”
mentioning
confidence: 99%